Love and Education. Love in Education - Amilburu, Maria (Paedagogia Christiana, 2025)
I will present in this paper some insights about the type of love that is needed in education according to some ideas presented by C. S. Lewis, Daniel Pennac, Joseph Rassam, Massimo Recalcati and François X. Bellamy, among others. After considering four anthropological assumptions that teachers must keep in mind for an adequate hermeneutics of human beings, education is presented like a kind of craftmanship, not as a mechanical production. This endeavour is understood as an act of love towards the students, and towards the wisdom that is condensed in the cultural traditions – scientific, humanistic, religious, artistic, etc. – we have inherited, and must pass improved to next generations, as their legitimate human inheritance.